Occurrence Mechanism and Controlling Factors of Shale Oil from the Paleogene Kongdian Formation in Cangdong Sag, Bohai Bay Basin, East China - Binyu Ma; Qinhong Hu; Xiugang Pu; Shengyu Yang; Xuyang Wang; Wenzhong Han; Jiacheng Wen (Journal of Marine Science and Engineering, 2024)
Free oil, rather than adsorbed oil, is the main contributor to shale oil production with current development technologies, and assessing oil contents in different occurrence states (adsorbed oil vs. free oil) is a critical component in evaluating the economics of shale wells and plays. Although various methodologies have been developed, there are still some fundamental issues in assessing the oil contents in different occurrence states in shale. In this study, a new method was developed to estimate the adsorbed and free oil contents in the Second Member of the Eocene Kongdian Formation (Ek2) shales in Cangdong Sag, Bohai Bay Basin. This method combines the results of standard Rock-Eval pyrolysis and multi-step Rock-Eval pyrolysis with thin section petrography, X-ray diffraction for mineralogy, total organic carbon analyses, field emission scanning electron microscopy for pore morphology, and pore structure analyses by nitrogen physisorption and mercury intrusion porosimetry. Nine lithofacies were identified in a total of 50 shale samples, and the results show that the adsorbed and free oil are mainly contained in pores with diameters > 20 nm, and their contents are mainly controlled by organic matter abundance and thermal maturity of shales. While pore space volume influences the storage of shale oil, it is not a major determinant. Models of shale oil occurrence and its evolution are proposed, suggesting that the high S1 contents of organic-rich and -fair shales, which the latter resulted from oil migration, are the most favorable exploration targets of Ek2 shales. The findings of this study will help prioritize shale oil exploration targets in Ek2 shales.